Plant cover as an estimator of above-ground biomass in semi-arid woody vegetation in Northeast Patagonia, Argentina - Rodríguez, Laura Belén (2021)
Fil: Rodríguez, Laura Belén. Universidad Nacional de Río Negro, Centro de Estudios Ambientales desde la NorPatagonia. Río Negro. Argentina